Three-dimensional measurement enabled by single-layer all-in-one transmitting-receipting optical metasystem - Xiaoli Jing; Qiming Liao; Misheng Liang; Bo Wang; Junjie Li; Yongtian Wang; Rui You; Lingling Huang (Opto-Electronic Advances, 2025)
Optical three-dimensional (3D) measurement is a critical tool in micro-nano manufacturing, the automotive industry, and medical technology due to its nondestructive nature, high precision, and sensitivity. However, passive light field system still requires a refractive primary lens to collect light of the scene, and structured light can not work well with the highly refractive object. Meta-optics, known for being lightweight, compact, and easily integrable, has enabled advancements in passive metalens-array light fields and active structured light techniques. Here, we propose and experimentally validate a novel 3D measurement metasystem. It features a transmitting metasurface generating chromatic line focuses as depth markers and a symmetrically arranged receiving metasurface collecting depth-dependent spectral responses. A lightweight, physically interpretable algorithm processes these data to yield high-precision depth information efficiently. Experiments on metallic and wafer materials demonstrate a depth accuracy of ±20 µm and lateral accuracy of ±10 µm. This single-layer optical metasystem, characterized by simplicity, micro-level accuracy, easy installation and scalability, shows potential for diverse applications, including process control, surface morphology analysis, and production measurement.